"Danger, Will Robinson!" The challenges of social robots for intergroup relations. Issue 8 (30th July 2019) - Vanman, Eric J.; Kappas, Arvid
Abstract: Society's increasing reliance on robots in everyday life provides exciting opportunities for social psychologists to work with engineers in the nascent field of social robotics. In contrast to industrial robots that, for example, may be used on an assembly line, social robots are designed specifically to interact with humans and/or other robots. People tend to perceive social robots as autonomous and capable of having a mind. As such, they are also more likely to be subject to social categorization by humans. As social robots become more human like, people may also feel greater empathy for them and treat robots more like (human) ingroup members. On the other hand, as they become more human like, robots also challenge our human distinctiveness, threaten our identity, and elicit suspicion about their ability to deceive us with their human‐like qualities. We review relevant research to explore this apparent paradox, particularly from an intergroup relations perspective. We discuss these findings and propose three research questions that we believe social psychologists are ideally suited to address.